Pengaruh Customer Trust Terhadap Customer Engagement Dan Swift Guanxi Dalam Live Streaming - Purnama, Jevon Keefe Purnama; Juliani Dyah Trisnawati; Siti Rahayu (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2025)
The increasing use of the internet has become a major driver of business transformation in the field of e-commerce. This phenomenon is relevant because live streaming interactions can build strong relationships between sellers and buyers, which can increase engagement and customer trust. The main challenges in e-commerce, including live streaming commerce, are maintaining product quality and avoiding fraud, which often results in decreased customer trust. This study aims to examine the effect of customer trust on customer engagement in the context of live streaming commerce, with swift guanxi as a mediating variable. The method used is Partial Least Square Structural Equation Modeling (PLS-SEM) with data from 333 Generation Z respondents who actively shop via live streaming. The results of the study show that Trust in Broadcasters and Trust in Community Members have a significant positive effect on Customer Engagement, while Trust in Products does not show a significant effect.